Heparin-induced cardiopulmonary arrest in a patient with heparin-induced thrombocytopenia: a rare severe anaphylactoid reaction - Breytenbach, Hekkie; Mohan, Sashen; Ensor, Jason; Gigi, Nkululo; Opie, Jessica; Haupt, Leriska; Peter, Jonny; Walton, Noel; Freercks , Robert (African Journal of Nephrology, 2025)
Heparin-induced thrombocytopenia (HIT) is a serious complication arising from heparin therapy, with features of thrombocytopenia and increased risk for thromboembolism. This report details cardiopulmonary arrest as an uncommon association of HIT in a 49-year-old female on chronic haemodialysis. Anaphylactoid reactions are reported in 1–4% of HIT cases and occur via non-IgE mediated mechanisms. This case also highlights the complexity of HIT diagnosis, with an initially negative platelet aggregation test later found to be positive at a reference laboratory. The patient was treated successfully with fondaparinux and warfarin, leading to a full recovery. We highlight the need for vigilance in recognizing HIT in dialysis patients and discuss some of the pitfalls relating to heparin-induced platelet aggregation testing.